Modern blocks : 99 quilt blocks from your favorite designers - Woods, Susanne (C. & T. Pub., 2011)
"The new kids on the block! Today's most talented modern quilters put a fresh and fun spin on 99 traditional block designs. Chock full of step-by-step instructions, how-to photographs and helpful hints, this collection of inspiring projects makes it easy for any sewer-no matter what level of expertise-to quilt in a modern style with impressive results"--